Digital Bodies: A controlled evaluation of a brief classroom‐based intervention for reducing negative body image among adolescents in the digital age. (4th August 2021) - Bell, Beth T.; Taylor, Caitlin; Paddock, Danielle; Bates, Adam
Abstract : Background: A growing body of research has linked social media use to negative body image. Aims: The present research aimed to evaluate the efficacy of Digital Bodies, a brief classroom‐based intervention that aims to improve adolescents' body image. Methods: British adolescents ( N  = 290; Age M  = 12.81; SD  = 0.40; Range  = 12–13; Female  = 151) were cluster randomized to intervention or waiting list control groups. Measures of body satisfaction, appearance ideal internalization (thin and athletic ideal internalization) and self‐objectification were completed at baseline (T1), 1‐week post‐intervention (T2) and 8‐week follow‐up (T3). Results: Multi‐level modelling showed adolescents in the intervention group reported improved body satisfaction at T2, in comparison to the control, and crucially this effect was sustained at T3. Additionally, girls reported less thin ideal internalization at T2 relative to the control, but this effect was not sustained at T3. No other intervention effects were found. Conclusions: Overall, the findings provide initial support for the efficacy of Digital Bodies as an intervention for improving adolescents' body satisfaction.